UPAYA PENCEGAHAN DAN PEMBERANTASAN KORUPSI PERSPEKTIF MAHASISWA - Dalisa Putri Ishaq; Dema Juliska; Riska Wandana (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Corruption is an extraordinary crime that has a wide impact on the life of the nation and state. Corrupt practices not only harm the state's finances, but also damage the legal system, weaken democracy, and hinder national development. In this context, students as the younger generation and agents of change have a strategic role in efforts to prevent and eradicate corruption. This research aims to analyze the role of students in building an anti-corruption culture through educational, preventive, and participatory approaches. The research method used is a qualitative approach with literature studies from various scientific sources such as journals, books, and official reports. The results of the study show that students have an important role as agents of change, agents of social control, and agents of education. In addition, students can also contribute through social movements, digital campaigns, and public policy supervision. In conclusion, the role of students is vital in creating a social system that is free from corruption. Therefore, synergy is needed between students, universities, the government, and the community in instilling the values of integrity and transparency in a sustainable manner.